Role of PPARγ in the Differentiation and Function of Neurons. (26th August 2014) - Quintanilla, Rodrigo A.; Utreras, Elias; Cabezas-Opazo, Fabián A.
Abstract : Neuronal processes (neurites and axons) have an important role in brain cells communication and, generally, they are damaged in neurodegenerative diseases. Recent evidence has showed that the activation of PPAR γ pathway promoted neuronal differentiation and axon polarity. In addition, activation of PPAR γ using thiazolidinediones (TZDs) prevented neurodegeneration by reducing neuronal death, improving mitochondrial function, and decreasing neuroinflammation in neuropathic pain. In this review, we will discuss important evidence that supports a possible role of PPAR γ in neuronal development, improvement of neuronal health, and pain signaling. Therefore, activation of PPAR γ is a potential target with therapeutic applications against neurodegenerative disorders, brain injury, and pain regulation.